Design Of Overheat Detection Device On Vehicle Engine Through Monitoring Water Temperature Or Cooling Oil - Nur Huda, Erfan; Zulfikar, Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Currently, there is a cooling system in vehicle engines that uses additional cooling which warns the driver that the engine's working temperature has exceeded a predetermined threshold, but not for older vehicles or those that still use a CDI (Capacitor Discharge Ignition) system that only relies on the cooling system. through the fins on the machine. To overcome the problems described previously, research was carried out. The result of this research is a tool or device that can detect excessive heat in a vehicle engine using the DS18B20 sensor. The temperature sensor results are processed using an NodeMCU ESP8266 Lolin microcontroller to obtain information about engine temperature. This tool provides a warning system with fan commands and an LCD display that shows the condition of the engine's working temperature at that time. With this tool, overheating of the engine can be prevented.